A SUGGESTION ON THE PAIR OF QSO TRIPLETS 1130+106 (B,A,C), (X,Y,Z) - Fagundes, H. (Univ Nacional Autonoma Mexico, Inst de Astronomia, 1990)
The alignment of a pair of QSO triplets discovered by Arp and Hazard are tentatively explained by a combination of (I) the idea of quasar ejection by galaxies; (II) a construction by Narlikar suggesting a common origin for the six images; and (III) a nontrivial topology of cosmic space.
Keywords: GRAVITATION; QUASARS